The Effect of Company Size, Investment Decisions and Funding Decisions on Company Value with Dividend Policy as a Moderation Variable - Wijaya, Santy; Subagyo, Ahmad; Ekawati, Christina; Hermawan, Hermawan (Jurnal Pendidikan Indonesia, 2025)
This study examines the influence of company size, investment decisions, and funding decisions on company value with dividend policy as a moderator in 20 companies in the consumer goods sub-sector on the IDX (2018-2023). The type of research used is explanatory research with a research method in the form of collecting data on financial statements of companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2023 period. The data analysis models used are multiple linear regression analysis and Moderated Regression Analysis (MRA). Sample selection was carried out by Purposive sampling. The sample totaled 20 companies, using multiple linear regression analysis and Moderated Regression Analysis (MRA). The results of MRA show that the dividend policy only moderates the relationship between funding decisions and the value of the company. These findings enrich the literature on dividend-based funding strategies in the consumption sector.